PENGEMBANGAN SISTEM DAN PELAKSANAAN TRACER STUDY ALUMNI IAIN PURWOKERTO TAHUN 2014-2016 - Suwito, Suwito; Yahya, Slamet; Hidayat, Arif (STKIP Pesisir Selatan, 2017)
This paper aims to reveal the relevance of the graduate education is shown through job profiles (occupations and occupations), job relevance with educational background, the benefits of courses programmed in the work, graduate advice for graduate competency improvement. In addition, the relevance of education is also demonstrated through the opinions of graduate users on graduate user satisfaction, graduate competence and graduate suggestions for graduate competency improvement. The result, the existence of job suitability in the hope that when college is also a matter of job satisfaction some feel satisfied with the work that is now being undertaken. The main consideration of alumni in work is not solely because salary factor is an interesting finding from this research. This can be seen in the graduates who become teachers (education sector) with a minimum salary, but in accordance with the field of science. In general, alumni income ranges from one million to three million per month. This is because they work to follow the minimum wage of district / city (UMK) which ranges from Rp. 1,000,000 - Rp. 3,000,000, although many are still under one million rupiah. Some alumni have worked before graduation, although in general IAIN alumni of Purwokerto year 2014-2016 work with 3 months waiting period. They are in the education sector.